Sulfur-carbon composite, positive electrode for lithium secondary battery and lithium secondary battery containing the same

By using porous carbon materials coated with thiophene-based polymers doped with dopant and sulfur-carbon composites in lithium sulfur batteries, the problem of shortening the life of lithium sulfur batteries caused by electrolyte decomposition is solved, and the reactivity and life of the battery are significantly improved.

CN113795946BActive Publication Date: 2025-02-28LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080033316.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-14
Filing Date
2020-05-29
Publication Date
2025-02-28
Estimated Expiration
2040-05-29

AI Technical Summary

Technical Problem

In lithium-sulfur batteries, the electrolyte decomposes on the surface of porous carbon materials, resulting in a shortening of the battery life.

Method used

The surface of the porous carbon material is coated with a thiophene-based polymer doped with a dopant to form a sulfur-carbon composite to prevent the decomposition of the electrolyte.

Benefits of technology

By preventing the decomposition of the electrolyte, the reactivity and life-span characteristics of lithium-sulfur batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113795946B_ABST
    Figure CN113795946B_ABST
Patent Text Reader

Abstract

The present invention relates to: a sulfur-carbon composite comprising a porous carbon material coated with a thiophene-based polymer doped with a dopant and sulfur in at least a portion of the interior and surface of the porous carbon material; and a positive electrode for a lithium secondary battery and a lithium secondary battery comprising the sulfur-carbon composite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2019-0070378, filed on Jun. 14, 2019, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a sulfur-carbon composite, and a positive electrode for a lithium secondary battery and a lithium secondary battery containing the same. Background Art

[0003] Recently, interest in energy storage technology has been increasing. As its application field expands to energy sources for mobile phones, camcorders, laptop computers, and even electric vehicles, more and more specific efforts are being made to research and develop electrochemical devices.

[0004] In this regard, electrochemical devices are the most noteworthy area, among which the development of secondary batteries capable of charge / discharge is the focus of attention. Recently, in developing these batteries, research and development have been conducted on the design of new electrodes and cells to improve capacity density and energy efficiency.

[0005] Among the secondary batteries currently in use, lithium secondary batteries developed in the early 1990s have attracted more attention because of their advantages in that their operating voltage and energy density are higher than those of conventional batteries such as Ni-MH, Ni-Cd and lead sulfate batteries using an electrolyte in the form of an aqueous solution.

[0006] In particular, lithium-sulfur (Li-S) batteries are secondary batteries that use a sulfur-based material with an SS bond (sulfur-sulfur bond) as a positive electrode active material and lithium metal as a negative electrode active material. The advantage of the lithium-sulfur battery is that sulfur, which is the main material of the positive electrode active material, has very abundant resources, is non-toxic, and has a low atomic weight. In addition, the theoretical discharge capacity of the lithium-sulfur battery is 1675mAh / g sulfur, and its theoretical energy density is 2600Wh / kg. Because the energy density of the lithium-sulfur battery is much higher than the theoretical energy density of other battery systems currently being studied (Ni-MH battery: 450Wh / kg, Li-FeS battery: 480Wh / kg, Li-MnO 2 Battery: 1000Wh / kg, Na-S battery: 800Wh / kg), so the lithium-sulfur battery is the most promising battery developed so far.

[0007] During the discharge of a lithium-sulfur battery, an oxidation reaction of lithium occurs at the negative electrode, and a reduction reaction of sulfur occurs at the positive electrode. Before discharge, sulfur has a cyclic S 8During the reduction reaction (discharge), the oxidation number of S decreases as the SS bond breaks, and during the oxidation reaction (charge), the oxidation number of S increases as the SS bond is formed again. The oxidation-reduction reactions described above are used to store and generate electrical energy. During these reactions, sulfur is removed from the cyclic S by reduction. 8 The structure is transformed into lithium polysulfide (Li 2 S x , x=8, 6, 4, 2) linear structure, and finally, when the lithium polysulfide is completely reduced, lithium sulfide (Li 2 S). Through the process of reduction to various lithium polysulfides, the discharge behavior of lithium-sulfur batteries shows a staged discharge voltage that is different from that of lithium-ion batteries.

[0008] However, in the case of such lithium-sulfur batteries, there is a problem of difficulty in commercialization due to low life characteristics.

[0009] This can be attributed to the fact that lithium polysulfide (LPS) dissolved from the positive electrode moves to the negative electrode, causing a side reaction directly on the negative electrode surface, thereby reducing the capacity of the battery and shortening the life. Another reason may be the fact that the electrolyte decomposes on the surface of the porous carbon material as the positive electrode active material, thus shortening the life due to the loss of the electrolyte.

[0010] Currently, a lot of research has been done on preventing the dissolution of lithium polysulfide, but research on preventing decomposition reactions in electrolytes is still insufficient.

[0011] Therefore, research is needed to improve the life characteristics of lithium-sulfur batteries by preventing the decomposition of the electrolyte.

[0012] Prior art literature

[0013] [Patent Document]

[0014] Korean Pending Patent Publication No. 10-2016-0134092 Summary of the invention

[0015] [Technical issues]

[0016] In the case of a lithium sulfur battery among lithium secondary batteries, there is a problem that an electrolyte decomposes on the surface of a porous carbon material of a sulfur-carbon composite used as a positive electrode active material, whereby the life of the lithium sulfur battery is shortened due to loss of the electrolyte.

[0017] As a result of various studies conducted to solve the above-mentioned problems, the inventors of the present invention have confirmed that if the surface of the porous carbon material of the sulfur-carbon composite is coated with a thiophene-based polymer doped with a dopant, the decomposition of the electrolyte can be prevented, thereby improving the life characteristics of the lithium-sulfur battery including the sulfur-carbon composite, thereby completing the present invention.

[0018] Therefore, an object of the present invention is to provide a sulfur-carbon composite capable of preventing decomposition of an electrolyte.

[0019] Another object of the present invention is to provide a positive electrode for a lithium secondary battery including the sulfur-carbon composite and a lithium secondary battery including the positive electrode.

[0020] [Technical solution]

[0021] In order to achieve the above-mentioned object, the present invention provides a sulfur-carbon composite, which comprises a porous carbon material and sulfur contained in at least a portion of the interior and surface of the porous carbon material, wherein the surface of the porous carbon material is coated with a thiophene-based polymer doped with a dopant.

[0022] In addition, the present invention provides a method for preparing a sulfur-carbon composite, the method comprising the following steps:

[0023] (a) coating a porous carbon material with a thiophene-based polymer doped with a dopant; and

[0024] (b) mixing the porous carbon material coated with the thiophene polymer doped with a dopant prepared in step (a) with sulfur and forming the mixture,

[0025] The present invention also provides a positive electrode for a lithium secondary battery comprising the sulfur-carbon composite of the present invention.

[0026] In addition, the present invention provides a lithium secondary battery, which includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is the positive electrode of the present invention.

[0027] Beneficial Effects

[0028] Since the surface of the porous carbon material is coated with the thiophene-based polymer doped with the dopant, the sulfur-carbon composite of the present invention can prevent the decomposition of the electrolyte, thereby improving the reactivity and life characteristics of the lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Graphs of the sulfur-carbon composites of Comparative Examples 1, 2, and 4 obtained by cyclic voltammetry.

[0030] Figure 2This is a graph obtained by measuring the life characteristics of Example 1, Example 2, Comparative Example 1, and Comparative Example 2.

[0031] Figure 3 This is a graph obtained by measuring the reactivity of the initial cycles of Example 1, Example 2, Comparative Example 1, and Comparative Example 2.

[0032] Figure 4 This is a graph obtained by measuring the life characteristics in the high-rate stage of Example 2 and Comparative Example 2.

[0033] Figure 5 This is a graph obtained by measuring the life characteristics of Example 3, Example 4, Comparative Example 1, and Comparative Example 3.

[0034] Best Mode

[0035] Hereinafter, the present invention will be described in more detail.

[0036] The term "composite" used herein refers to a material in which two or more materials are combined to exhibit more effective functions while forming phases that are physically and chemically different from each other.

[0037] In the case of lithium secondary batteries, especially lithium sulfur batteries, decomposition of the electrolyte occurs on the surface of the porous carbon material of the sulfur-carbon composite as the positive electrode active material, and more specifically, because sulfur decomposes first, decomposition of the electrolyte occurs in the porous carbon material remaining after the decomposition of sulfur. As the electrolyte decomposes, the electrolyte is consumed, and thus there is a problem of shortening the life of the lithium sulfur battery.

[0038] Therefore, the present invention provides a sulfur-carbon composite that can solve the above-mentioned problems.

[0039] Sulfur-carbon complex

[0040] The present invention relates to a sulfur-carbon composite comprising a porous carbon material and sulfur contained in at least a portion of the interior and surface of the porous carbon material, wherein the surface of the porous carbon material is coated with a thiophene-based polymer doped with a dopant.

[0041] In the present invention, since the surface of the porous carbon material is coated with a thiophene polymer doped with a dopant, the electrolyte can be prevented from decomposing on the surface of the porous carbon material, thereby improving the problem of shortening the life of the lithium secondary battery due to the loss of the electrolyte and improving the reactivity.

[0042] The porous carbon material may have a porous structure or a high specific surface area, and may be any porous material conventionally used in the art. The porous carbon material may preferably include at least one selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon fibers and activated carbon, and may preferably include carbon nanotubes.

[0043] The polymer coated on the surface of the porous carbon material is a conductive polymer, and in the present invention, a thiophene-based polymer doped with a dopant is coated on the surface of the porous carbon material.

[0044] The thiophene-based polymer is most preferable because it is a water-based conductive polymer and can coat the surface of a porous carbon material even in a small amount.

[0045] The thiophene-based polymer is not particularly limited in type, but may preferably include at least one selected from the group consisting of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT:PSS) and poly(3-hexylthiophene).

[0046] Poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate is a polymer obtained by dispersing poly(3,4-ethylenedioxythiophene) having low solubility in water or an organic solvent using polystyrene sulfonate having high solubility in water. Poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate can improve lithium ion conductivity through the sulfonic group of polystyrene sulfonate, and can also be used as a dopant to improve electron conductivity. In addition, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate is easily mixed with a volatile solvent and is most effective for preventing decomposition of an electrolyte. Therefore, among thiophene-based polymers, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate is most preferably used.

[0047] In addition, the dopant may include at least one selected from the group consisting of sulfuric acid, p-toluenesulfonic acid, perchloric acid, hydrochloric acid, fluoroboric acid, and phosphoric acid, and preferably may include at least one selected from the group consisting of sulfuric acid and p-toluenesulfonic acid.

[0048] By doping the thiophene-based polymer with a dopant, the conductivity can be improved, thereby providing a lithium secondary battery, preferably a lithium-sulfur battery, having excellent life characteristics and reactivity.

[0049] Generally, when the charges of positive and negative charges are the same, the electronic conductivity is reduced due to the stability of the charge. When doped with a dopant, the overvoltage of the battery can be reduced because the conductivity is increased due to the imbalance between the positive and negative charges, and the side reaction can be reduced by reducing the reaction time between lithium and the positive electrode active material. In addition, as the reaction time is shortened, the C rate characteristics can be improved. Thus, a lithium secondary battery, preferably a lithium-sulfur battery, having excellent life characteristics and reactivity can be provided.

[0050] The content of the dopant is 0.01 to 10 parts by weight, preferably 0.01 to 1 part by weight, based on 100 parts by weight of the thiophene-based polymer.

[0051] If the dopant is less than 0.01 parts by weight, the effect of improving electron conductivity caused by the dopant is insufficient. If the dopant exceeds 10 parts by weight, the conductivity may be reduced by disturbing the imbalance of charges.

[0052] The pH of the thiophene-based polymer doped with the dopant may be 2 to 7, preferably 4 to 6. If the pH is outside the range, there is a problem of reduced electron conductivity, and problems such as electrode corrosion may occur in strong acids or bases.

[0053] Since the sulfur-carbon composite has a structure in which carbon particles are contained inside and outside sulfur particles, there is an advantage that sulfur and carbon can be mixed in a uniform ratio, so that carbon as a conductive material can effectively impart electronic conductivity to sulfur.

[0054] Sulfur may include sulfur (S 8 )、Li 2 S n (n≥1), organic sulfur compounds and carbon-sulfur polymers ((C 2 S x ) n : at least one of the group consisting of x=2.5-50, n≥2).

[0055] In addition, the diameter of the sulfur-carbon composite 11 may be 5 μm to 100 μm, preferably 10 μm to 70 μm, and more preferably 15 μm to 60 μm. In this case, the diameter of the sulfur-carbon composite 11 refers to the length of the longest axis in the cross section of the particle. If the diameter of the sulfur-carbon composite is less than 5 μm, the porosity of the electrode is very low, and the reactivity of the electrode is reduced. If the diameter of the sulfur-carbon composite exceeds 100 μm, the unevenness during electrode formation increases, which may cause problems such as the occurrence of short circuits and an increase in porosity.

[0056] The weight ratio of sulfur to the porous carbon material coated with the thiophene-based polymer doped with the dopant may be 60:40 to 90:10, preferably 65:35 to 85:15, and more preferably 70:30 to 80:20. If the weight ratio of the porous carbon material to sulfur is less than the above range, the conductivity may be deteriorated. If the weight ratio of the porous carbon material to sulfur exceeds the above range, the amount of active material may be reduced and the energy density may be reduced.

[0057] Method for preparing sulfur-carbon composite

[0058] In addition, the present invention relates to a method for preparing a sulfur-carbon composite, the method comprising the following steps:

[0059] (a) coating a porous carbon material with a thiophene-based polymer doped with a dopant; and

[0060] (b) mixing the porous carbon material coated with the thiophene-based polymer doped with a dopant prepared in step (a) with sulfur and forming the mixture.

[0061] The step (a) is a step of coating the porous carbon material with the thiophene-based polymer doped with a dopant.

[0062] The dopant, the thiophene-based polymer and the porous carbon material are the same as those described above.

[0063] There is no particular limitation on coating as long as it is a coating method used in the art for forming a coating layer, and may be formed by wet coating, droplet casting, dip coating, blade coating, spray coating, meyer bar coating, or vacuum filter coating.

[0064] When a solvent is required for coating, water or an organic solvent such as ethanol, acetone, isopropyl acetate (IPA), tetrahydrofuran (THF), dichloromethane (MC), dimethylformamide (DMF), dimethyl sulfoxide (DMSO) and dimethylacetamide (DMAc) and the like can be listed.

[0065] In addition, when the surface of the porous carbon material is coated with a thiophene polymer doped with a dopant, the bonding at the interface between the coating layer containing the copolymer and the porous carbon material is achieved by the reaction between the copolymer and the carbon (bonding by π-π interaction). At this time, the reaction can be carried out at room temperature to 100° C., preferably at 40° C. to 70° C. for 1 hour to 24 hours.

[0066] Step (b) is a step of preparing a sulfur-carbon composite by mixing the porous carbon material coated with the thiophene-based polymer doped with a dopant prepared in step (a) with sulfur and molding the mixture.

[0067] The method of mixing and shaping sulfur may be any method as long as it is a method known in the art.

[0068] The purpose of mixing is to increase the mixing degree between the above materials, and can be implemented using a stirring device commonly used in the art. At this time, the mixing time and speed can also be selectively adjusted according to the content and conditions of the raw materials.

[0069] The heating temperature may be any temperature at which sulfur melts, and specifically may be 120° C. to 180° C., preferably 150° C. to 180° C. If the heating temperature is lower than 120° C., the structure of the sulfur-carbon composite may not be properly formed because the sulfur is not sufficiently melted. If the heating temperature exceeds 180° C., it is difficult to obtain the desired effect because the coated compound does not remain. In addition, the heating time can be adjusted according to the sulfur content.

[0070] Through the step (b), the sulfur-carbon composite can be prepared, and the porous carbon material is coated with the thiophene-based polymer doped with the dopant on the surface.

[0071] Positive electrode of lithium secondary battery

[0072] The present invention also relates to a positive electrode for a lithium secondary battery, preferably a positive electrode for a lithium sulfur battery, comprising the sulfur-carbon composite of the present invention. The sulfur-carbon composite is a positive electrode active material.

[0073] The positive electrode may include a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, and the positive electrode active material layer may include a positive electrode active material and optionally a conductive material and a binder.

[0074] In order to allow electrons to move smoothly within the positive electrode, a conductive material may be included together with the positive electrode active material, and in order to improve adhesion between the positive electrode active materials or between the positive electrode active material and the current collector, a binder may be included.

[0075] The positive electrode current collector can generally be made into a thickness of 3 μm to 500 μm, and there is no particular limitation as long as it has high conductivity and does not cause chemical changes in the battery. For example, conductive metals such as stainless steel, aluminum, copper or titanium can be used as positive electrode current collectors, and preferably aluminum current collectors can be used. The positive electrode current collector can be formed in various forms such as films, sheets, foils, nets, porous bodies, foams or non-woven fabrics.

[0076] The conductive material may be: a carbon-based material such as carbon black, acetylene black and ketjen black; a conductive polymer such as polyaniline, polythiophene, polyacetylene, polypyrrole, and the content of the conductive material is preferably 5 wt % to 20 wt % based on the total weight of the positive electrode active material layer. If the content of the conductive material is less than 5 wt %, the effect of improving the conductivity by using the conductive material is not obvious. On the other hand, if the content of the conductive material exceeds 20 wt %, the content of the positive electrode active material becomes relatively small, and thus the capacity characteristics may be deteriorated.

[0077] In addition, the binder can be poly (vinyl acetate), polyvinyl alcohol, polyethylene oxide, polyvinyl pyrrolidone, alkylated polyethylene oxide, cross-linked polyethylene oxide, polyvinyl ether, poly (methyl methacrylate), polyvinylidene fluoride, polyhexafluoropropylene and polyvinylidene fluoride copolymer (product name: Kynar), poly (ethyl acrylate), polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyvinyl pyridine, polystyrene and its derivatives, blends and copolymers, etc. In addition, based on the total weight of the positive electrode active material layer, the content of the binder may preferably be 5% to 20% by weight. If the content of the binder is less than 5% by weight, the effect of increasing the adhesion between the positive electrode active materials or between the positive electrode active materials and the collector due to the use of the binder is insufficient. On the other hand, if the content of the binder exceeds 20% by weight, the content of the positive electrode active material becomes relatively less, so the capacity characteristics may deteriorate.

[0078] The positive electrode as described above can be manufactured by a conventional method, specifically, by applying a composition for forming a positive electrode active material layer onto a current collector, and then drying and optionally rolling, the composition being prepared by mixing a positive electrode active material, a conductive material and a binder in an organic solvent or water.

[0079] At this time, the organic solvent may be a solvent that can uniformly disperse the positive electrode active material, the binder and the conductive material and evaporate easily. Specifically, the organic solvent may include acetonitrile, methanol, ethanol, tetrahydrofuran, isopropanol, and the like.

[0080] Lithium secondary battery

[0081] The present invention relates to a lithium secondary battery, comprising a positive electrode, a negative electrode, a separator arranged between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is the positive electrode of the present invention described above.

[0082] The lithium secondary battery may preferably be a lithium-sulfur battery.

[0083] The negative electrode may be composed of a current collector and a negative electrode active material layer formed on one or both surfaces thereof. In addition, the negative electrode may be a lithium metal plate.

[0084] The current collector is used to support the negative electrode active material, and is not particularly limited as long as it is electrochemically stable within the voltage range of the lithium secondary battery while having excellent conductivity. For example, as the current collector, copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon; copper or stainless steel surface-treated with carbon, nickel, silver, etc.; aluminum-cadmium alloy, etc. can be used.

[0085] The negative electrode current collector strengthens the bonding force with the negative electrode active material by forming fine concavoconvexities on the surface thereof, and may be formed in various forms such as a film, a sheet, a foil, a screen, a net, a porous body, a foam body, or a nonwoven fabric.

[0086] The negative electrode active material may include a material capable of reversibly intercalating or deintercalating lithium ions, a material capable of reversibly forming a lithium-containing compound by reacting with lithium ions, or lithium metal or a lithium alloy.

[0087] The material capable of reversibly intercalating or deintercalating lithium ions can be, for example, crystalline carbon, amorphous carbon, or a mixture thereof.

[0088] The material capable of reacting with lithium ions to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon.

[0089] The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al) and tin (Sn).

[0090] A separator is also included between the positive electrode and the negative electrode. The separator separates or insulates the positive electrode and the negative electrode from each other and enables lithium ions to be transferred between the positive electrode and the negative electrode, and may be made of a porous non-conductive or insulating material. Such a separator may be an independent component such as a film, and may be a coating added to the positive electrode and / or the negative electrode.

[0091] Materials forming the separator include, but are not limited to, for example: polyolefins such as polyethylene and polypropylene; glass fiber filter paper; and ceramic materials, and the thickness thereof may be about 5 μm to about 50 μm, preferably about 5 μm to about 25 μm.

[0092] The electrolyte solution as a non-aqueous electrolyte containing a lithium salt is composed of a lithium salt and an electrolytic solution. A non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, or the like is used as the electrolytic solution.

[0093] There is no particular limitation on the lithium salt, as long as it can be conventionally used in the electrolyte of a lithium secondary battery, preferably a lithium sulfur battery. For example, a lithium salt selected from LiSCN, LiBr, LiI, LiPF 6 , LiBF 4 , LiB10 Cl 10 、LiSO 3 CF 3 、LiCl、LiClO 4 、LiSO 3 CH 3 、LiB(Ph) 4 、LiC(SO 2 CF 3 ) 3 、LiN(SO 2 CF 3 ) 2 、LiCF 3 CO 2 、LiAsF 6 、LiSbF 6 、LiAlCl 4 , LiFSI, lithium chloroborane, lower aliphatic lithium carbonate, etc.

[0094] In addition, the concentration of the lithium salt in the electrolyte may be 0.2M to 2M, specifically 0.6M to 2M, and more specifically 0.7M to 1.7M. If the concentration of the lithium salt is less than 0.2M, the conductivity of the electrolyte may decrease, and thus the performance of the electrolyte may deteriorate. If the concentration of the lithium salt exceeds 2M, the viscosity of the electrolyte may increase, and thus the mobility of lithium ions may decrease.

[0095] The non-aqueous organic solvent should dissolve the lithium salt well, and the non-aqueous organic solvent of the present invention may include, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, 4-methyl-1 , 3-dioxane, diethyl ether, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate and ethyl propionate, and these organic solvents can be used alone or in the form of a mixed solvent of two or more thereof.

[0096] As the organic solid electrolyte, for example, polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyalginate lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers having ion dissociative groups, and the like can be used.

[0097] As the inorganic solid electrolyte, for example, Li nitride, halide, sulfate, etc. can be used, such as Li 3 N, LiI, Li 5 NI 2 , Li 3 N-LiI-LiOH, LiSiO 4 、LiSiO 4 -LiI-LiOH, Li 2 SiS 3 , Li 4 SiO 4 , Li 4 SiO 4 -LiI-LiOH, Li 3 PO 4 -Li2 S -SiS 2 .

[0098] In order to improve the charge / discharge characteristics, flame retardancy, etc., pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N, N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum chloride, etc. In some cases, in order to impart non-flammability, a halogen-containing solvent such as carbon tetrachloride, trifluoroethylene, etc. can also be added, and in order to improve storage characteristics at high temperatures, carbon dioxide gas can be further contained, and FEC (fluoroethylene carbonate), PRS (propylene sultone), FPC (fluoropropylene carbonate), etc. can also be contained.

[0099] The electrolyte can be used as a liquid electrolyte or in the form of a solid electrolyte membrane. When used as a liquid electrolyte, it also includes a membrane made of porous glass, plastic, ceramic or polymer as a physical membrane with the function of physically separating the electrodes.

[0100] The lithium secondary battery of the present invention, preferably the lithium sulfur battery, comprises the sulfur-carbon composite of the present invention as a positive electrode active material. Since the surface of the porous carbon material of the sulfur-carbon composite is coated with a thiophene polymer doped with a dopant, the electrolyte can be prevented from decomposing on the surface of the porous carbon material, thereby solving the problem of the life of the lithium secondary battery being deteriorated due to the loss of the electrolyte, thereby improving the life characteristics of the lithium secondary battery and increasing the reactivity.

[0101] In the following, preferred examples are provided to help understand the present invention, but the following examples are only for illustration of the present invention, and it is obvious to those skilled in the art that various changes and modifications can be made within the scope and technical spirit of the present invention, and such changes and modifications naturally also belong to the attached claims.

[0102] <Preparation of Sulfur-Carbon Composite>

[0103] Example 1

[0104] To poly (3,4-ethylenedioxythiophene) - polystyrene sulfonate (PEDOT:PSS) (from Heraeus Clevios TM ) dropwise add sulfuric acid (H 2 SO 4 ), whereby the surface of PEDOT:PSS is doped with sulfuric acid.

[0105] The pH of PEDOT:PSS doped with sulfuric acid is 6-7.

[0106] In order to make coating easier, ethanol was added to an aqueous solution of PEDOT:PSS doped with sulfuric acid to prepare a PEDOT:PSS coating solution. Carbon nanotubes were added to the coating solution and stirred to prepare carbon nanotubes coated with PEDOT:PSS doped with sulfuric acid.

[0107] At this time, the PEDOT:PSS doped with sulfuric acid was applied in an amount of 2 parts by weight based on 100 parts by weight of the carbon nanotubes.

[0108] After the carbon nanotubes coated with PEDOT:PSS doped with sulfuric acid were uniformly mixed with sulfur, they were heat treated at 155° C. for 30 minutes to prepare a sulfur-carbon composite. The weight ratio of the carbon nanotubes coated with PEDOT:PSS doped with sulfuric acid to sulfur was 8:2.

[0109] Example 2

[0110] A sulfur-carbon composite was prepared in the same manner as in Example 1, except that p-toluenesulfonic acid was used instead of sulfuric acid.

[0111] Example 3

[0112] A sulfur-carbon composite was prepared in the same manner as in Example 1, except that the same procedure as in Example 1 was performed, but the pH of the PEDOT:PSS doped with sulfuric acid was 2.

[0113] Example 4

[0114] A sulfur-carbon composite was prepared in the same manner as in Example 1, except that the same procedure as in Example 1 was performed, but the pH of the PEDOT:PSS doped with sulfuric acid was 5.

[0115] Comparative Example 1

[0116] After the carbon nanotubes and sulfur were uniformly mixed, they were heat treated at 155° C. for 30 minutes to prepare a sulfur-carbon composite.

[0117] Comparative Example 2

[0118] A sulfur-carbon composite was prepared in the same manner as in Example 1 except that sulfuric acid was not used.

[0119] Comparative Example 3

[0120] After the carbon nanotubes and sulfur were uniformly mixed, they were heat treated at 155°C for 30 minutes to prepare a sulfur-carbon composite. Thereafter, PEDOT:PSS was coated on the surface of the sulfur-carbon composite, and at this time, 2 parts by weight of PEDOT:PSS was coated based on 100 parts by weight of the sulfur-carbon composite to prepare the sulfur-carbon composite.

[0121] Comparative Example 4

[0122] Polyethylene glycol (PEO) was coated on the surface of the carbon nanotube, and at this time, PEO was coated in an amount of 2 parts by weight based on 100 parts by weight of the carbon nanotube.

[0123] After the carbon nanotubes coated with PEO were uniformly mixed with sulfur, they were heat treated at 155° C. for 30 minutes to prepare a sulfur-carbon composite, and the weight ratio of sulfur to the carbon nanotubes coated with PEO was 8:2.

[0124] Experimental Example 1. Decomposition measurement of electrolyte solution for positive electrode of lithium-sulfur battery

[0125] By using the sulfur-carbon composites prepared in Comparative Examples 1, 2, and 4 as a positive electrode active material, each positive electrode for a lithium-sulfur battery was prepared.

[0126] The slurry was prepared by mixing the sulfur-carbon composite, the conductive material and the binder in a weight ratio of 90:5:5 for the sulfur-carbon composite: the conductive material: the binder, and then coated on an aluminum foil collector with a thickness of 20 μm to manufacture an electrode. At this time, carbon black was used as a conductive material, and styrene-butadiene rubber and carboxymethyl cellulose were used as binders. Subsequently, the positive electrode was manufactured by drying in an oven at 50°C overnight.

[0127] Cyclic voltammetry was performed to observe the decomposition of the sulfur-carbon complex electrolyte. When a voltage of 1.0 V to 2.0 V was applied while changing the scan rate within the range of 20 mV / s to 200 mV / s, the current value measured at the working electrode was recorded and the results are shown in Figure 1 middle.

[0128] As can be seen from the above results, in the case of Comparative Example 1 using the sulfur-carbon composite prepared using carbon nanotubes without the thiophene-based polymer, the electrolyte was decomposed.

[0129] It has been confirmed that in the case of Comparative Example 2 using the sulfur-carbon composite containing carbon nanotubes coated with PEDOT:PSS, the potential band and its width is greatly reduced, and from this it can be seen that decomposition of the electrolyte can be prevented.

[0130] In addition, it can be seen that compared with Comparative Example 1, the sulfur-carbon composite containing carbon nanotubes coated with PEO prepared in Comparative Example 4 prevented the decomposition of the electrolyte, but compared with Comparative Example 2, the sulfur-carbon composite containing carbon nanotubes coated with PEO prepared in Comparative Example 4 did not prevent the decomposition of the electrolyte.

[0131] Experimental Example 2. Determination of life characteristics of lithium-sulfur batteries

[0132] Using the sulfur-carbon composites prepared in Examples 1 to 4 and Comparative Examples 1 to 3 as positive electrode active materials, lithium-sulfur batteries were manufactured.

[0133] The slurry was prepared by mixing the sulfur-carbon composite, the conductive material and the binder in a weight ratio of 90:5:5 for the sulfur-carbon composite: the conductive material: the binder, and then coated on an aluminum foil collector with a thickness of 20 μm to manufacture an electrode. At this time, carbon black was used as a conductive material, and styrene-butadiene rubber and carboxymethyl cellulose were used as binders. Subsequently, the positive electrode was manufactured by drying in an oven at 50°C overnight.

[0134] A coin cell was manufactured using the electrode manufactured as above as the positive electrode, polyethylene as the separator, and lithium foil having a thickness of 45 μm as the negative electrode. At this time, the coin cell used a mixture of 1 M LiTFSI and 3 wt % LiNO 3 The electrolyte prepared by dissolving in an organic solvent composed of DOL / DME solvent (volume ratio of 1:1). Here, DOL refers to dioxolane and DME refers to dimethoxyethane.

[0135] Life characteristics were measured by performing charge / discharge at 0.1C / 0.1C for the first 3 cycles and performing charge / discharge at 0.2C / 0.2C for 3 cycles using a charge / discharge measurement device, and then repeating charge / discharge at 0.3C / 0.5C.

[0136] In the case of Comparative Example 4, since the sulfur-carbon composite was separated due to cracks generated in the electrode, it was difficult to manufacture a lithium-sulfur battery.

[0137] In the results of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 ( Figure 2 ), it has been confirmed that the sulfur-carbon composite containing carbon nanotubes coated with PEDOT:PSS prepared in Comparative Example 2 has more excellent reactivity and improved life characteristics compared with the sulfur-carbon composite of Comparative Example 1. Therefore, it was found that coating the porous carbon material with PEDOT:PSS improves the life characteristics and reactivity of the lithium-sulfur battery.

[0138] The sulfur-carbon composite containing carbon nanotubes coated with PEDOT:PSS doped with sulfuric acid prepared in Example 1 showed higher reactivity than the sulfur-carbon composite containing carbon nanotubes coated with PEDOT:PSS doped with p-toluenesulfonic acid prepared in Example 2. Thus, it was found that sulfuric acid is most preferred as a dopant.

[0139] In addition, Example 1 has more excellent reactivity and life characteristics than Comparative Examples 1 and 2, and Example 2 is better than Comparative Example 1, but shows similar results of reactivity and life characteristics to Comparative Example 2.

[0140] However, according to the results of the initial reaction stage of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 ( Figure 3 ), it has been confirmed that Example 1 and Example 2 have better reactivity than Comparative Example 1 and Comparative Example 2.

[0141] In addition, in the evaluation of the life characteristics at the high rate stage of Example 2 and Comparative Example 2 ( Figure 4 ), Example 2 shows better life characteristics than Comparative Example 2.

[0142] Therefore, it can be seen that the sulfur-carbon composite containing the carbon nanotubes coated with PEDOT:PSS doped with the dopant has excellent reactivity and lifespan characteristics.

[0143] In the results of Example 3, Example 4, Comparative Example 1 and Comparative Example 3 ( Figure 5), Comparative Example 3 in which the surface of the sulfur-carbon composite was coated with PEDOT:PSS showed very poor results of life characteristics. Compared with Comparative Examples 1 and 3, Example 3 in which the pH of PEDOT:PSS doped with sulfuric acid was 2 and the sulfur-carbon composite was prepared using the carbon nanotubes coated therewith had better life characteristics. Compared with Example 3, Example 4 in which the pH of PEDOT:PSS doped with sulfuric acid was 5 and the sulfur-carbon composite was prepared using the carbon nanotubes coated therewith showed more excellent reactivity and life characteristics.

[0144] Therefore, it has been found that a pH of 5 for PEDOT:PSS doped with sulfuric acid is most preferred.

[0145] The present invention relates to a sulfur-carbon composite, which contains: a porous carbon material coated with a thiophene polymer doped with a dopant and sulfur. The sulfur-carbon composite can prevent the decomposition of an electrolyte through the above coating, thereby improving the reactivity and life characteristics of a lithium-sulfur battery containing the sulfur-carbon composite.

Claims

1. A method for preparing a sulfur-carbon composite, the method comprising the following steps: (a) coating a porous carbon material with a thiophene-based polymer doped with a dopant; and (b) mixing the porous carbon material coated with the thiophene polymer doped with a dopant prepared in step (a) with sulfur and forming the mixture, The dopant includes at least one selected from the group consisting of sulfuric acid, p-toluenesulfonic acid, perchloric acid, hydrochloric acid, fluoroboric acid, and phosphoric acid.

2. A sulfur-carbon composite, which can be obtained by the method of claim 1, The sulfur-carbon composite comprises a porous carbon material and sulfur contained in at least a portion of the interior and surface of the porous carbon material, wherein the surface of the porous carbon material is coated with a thiophene-based polymer doped with a dopant, The dopant comprises at least one selected from the group consisting of sulfuric acid, p-toluenesulfonic acid, perchloric acid, hydrochloric acid, fluoroboric acid and phosphoric acid, The thiophene-based polymer doped with a dopant is only coated on the surface of the porous carbon material. 3 . The sulfur-carbon composite according to claim 2 , wherein the thiophene-based polymer comprises at least one selected from the group consisting of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate and poly(3-hexylthiophene). 4 . The sulfur-carbon composite according to claim 2 , wherein the content of the dopant is 0.01 parts by weight to 10 parts by weight based on 100 parts by weight of the thiophene-based polymer. 5 . The sulfur-carbon composite according to claim 2 , wherein the porous carbon material comprises at least one selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon fibers, and activated carbon. 6 . The sulfur-carbon composite according to claim 2 , wherein the pH of the thiophene-based polymer doped with a dopant is 2 to 7.

7. The sulfur-carbon composite according to claim 2, wherein the sulfur comprises sulfur S8; Li2S n ,in, n≥1; organic sulfur compounds; and by (C2S x ) n At least one of the group consisting of a carbon-sulfur polymer represented by x=2.5-50 and n≥2. 8 . A positive electrode for a lithium secondary battery, comprising the sulfur-carbon composite according to claim 2 . 9 . The positive electrode for a lithium secondary battery according to claim 8 , wherein the positive electrode for a lithium secondary battery is a positive electrode for a lithium-sulfur battery. 10 . A lithium secondary battery, comprising: a positive electrode; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode is the positive electrode according to claim 8 or 9 . The lithium secondary battery according to claim 10 , wherein the lithium secondary battery is a lithium sulfur battery.

Citation Information

Patent Citations

  • Organometallic compound and organic light emitting device comprising the same

    KR1020190070378A

  • Lithium battery with polymer-coated sulfur / carbon composite material as anode

    CN102447113A

  • Positive electrode active material for polyvalent ion secondary batteries, positive electrode for polyvalent ion secondary batteries, polyvalent ion secondary battery, battery pack, electric vehicle, electrical energy storage system, electric tool and electronic device

    CN109104882A

  • Sulfur-carbon composite, method for preparing same, and lithium secondary battery comprising same

    CN112470309A

  • Sulfur-carbon composite and lithium-sulfur battery including the same

    KR1020180017975A